Analisis Manajemen Risiko pada UMKM Warung Nasi Wicipi - Nur Fadila, Aulia; Nabila, Afifa (Jurnal Serambi Ekonomi dan Bisnis, 2024)
Risk management is an important process in ensuring business sustainability, including in the MSME sector such as rice stalls. This research analyzes the risks faced by Warung Nasi “Wicipi,” including capital, financial, operational, human resources (HR), and external risks. The research method used is a qualitative approach through in-depth interviews and direct observation. The results of the analysis show that capital limitations, income fluctuations, lack of employee skills, and market competition are the main challenges. Recommended mitigation strategies include funding diversification, employee training, mature financial management, and product innovation to adjust to market trends. This research confirms the importance of implementing effective risk management to improve the competitiveness and sustainability of MSMEs in the face of evolving market dynamics.